Dexamethasone induces docetaxel and cisplatin resistance partially through up-regulating Krüppel-like factor 5 in triple-negative breast cancer - Li, Zhen (Oncotarget, 2016)
PURPOSE: Dexamethasone (Dex), a glucocorticoid (GC), is used as a pretreatment drug in cancer patients undergoing chemotherapy. Dex functions by binding to the glucocorticoid receptor (GR) to prevent allergic reactions and severe chemotherapeutic side effects such as nausea and vomiting. However, the mechanisms by which Dex causes chemoresistance remain unknown. METHODS: We used docetaxel and cisplatin to treat triple-negative breast cancer (TNBC) cells with or without Dex and assessed cell proliferation using a sulforhodamine B colorimetric (SRB) assay. Additionally, Western blotting was employed to measure Krüppel-like factor 5 (KLF5), GR and several apoptosis-related proteins. To determine how the GR regulates KLF5, we used qRT-PCR, luciferase reporter assays and ChIP assays. Finally, we detected the involvement of Dex in TNBC chemotherapeutic resistance using HCC1806 xenograft model in vivo. RESULTS: In this study, we demonstrated that Dex induces docetaxel and cisplatin resistance in TNBC cells in vitro and in vivo. Dex up-regulates pro-survival transcription factor KLF5 expression at both mRNA and protein levels dependent on GR. Importantly, Dex failed to promote cancer cell survival and tumor growth when KLF5 induction was blocked. CONCLUSIONS: We conclude that KLF5 is a Dex-induced gene that contributes to Dex-mediated drug chemoresistance, providing a potential novel target for TNBC treatment.